Disclosure to South African children about their own HIV status over time. Issue 3 (4th March 2023) - Wu, Melody; Shiau, Stephanie; Strehlau, Renate; Liberty, Afaaf; Patel, Faeezah; Burke, Megan; Murnane, Pamela M.; Violari, Avy; Yin, Michael T.; Abrams, Elaine J.; Kuhn, Louise; Arpadi, Stephen
ABSTRACT: Disclosure to children living with HIV (CLHIV) about their own status is associated with positive outcomes such as treatment adherence, but prior cross-sectional studies in sub-Saharan Africa report disclosure rates of <50%. This study aims to assess pediatric disclosure over time. 548 CLHIV were followed from 2/2013–4/2018 in Johannesburg, South Africa. Cumulative incidence of disclosure was calculated with Kaplan-Meier analysis, and disclosure characteristics assessed with a Cox model. By end of follow-up, cumulative disclosure was 70.3% (95% confidence interval: 60.0–79.9). Median age at disclosure was 9 years (range: 3–13). Baseline predictors of disclosure included older child age and the child having a history of going hungry. Prior to disclosure, 98.0% of caregivers who disclosed had conversed with their child about their illness or an HIV-related topic, or their child had asked about HIV, versus 88.6% of caregivers who never disclosed. While many children did not receive disclosure during this relatively large, longitudinal study of South African CLHIV, caregivers who had not yet disclosed may have been preparing to do so by discussing their child's health or HIV generally with their child. This highlights the need for clinicians to consistently support caregivers throughout the incremental disclosure process.